Alternation of Pore Architecture of Ziegler–Natta Catalysts through Modification of Magnesium Ethoxide. Issue 4 (27th March 2015) - Funako, Toshiki; Chammingkwan, Patchanee; Taniike, Toshiaki; Terano, Minoru
<x xml:space="preserve">Abstract</x> The present article proposes a simple way to dramatically alter the pore architecture of Mg(OEt)2‐based Ziegler–Natta catalysts by the addition of a small amount of i‐propanol during the synthesis of Mg(OEt)2. The incorporated i‐propoxide distorts the crystalline structure of Mg(OEt)2, finally causing the phase transformation and significant densification of particles. Such modifications completely alternate the pore architecture of resultant catalysts, which contribute to the design of catalytic properties.<inline-graphic xlink:href="ark:/27927/pgj2fh7xsxd" content-type="mren201400074-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />